Multiplatform, Multidisciplinary Investigations of the Impacts of Modified Circumpolar Deep Water in the Ross Sea, Antarctica - Walker O. Smith Jr; Kimberly T. Goetz; Daniel E. Kaufman; Bastien Y. Queste; Vernon Asper; Daniel P. Costa; Michael S. Dinniman; Marjorie A.M. Friedrichs; Eileen E. Hofmann; Karen J. Heywood; John M. Klinck; Josh T. Kohut; et al. (Oceanography, 2014)
In 2010–2011, three projects combined to characterize the temporal and spatial distributions of Modified Circumpolar Deep Water (MCDW) in the Ross Sea using icebreaker-based sampling, gliders, instrumented seals, and hindcasts from a numerical circulation model. The fieldwork clearly identified MCDW throughout the Ross Sea, and the data were used to determine its influence on potential heat and nutrient inputs and biotic distributions. Furthermore, the numerical simulations confirm its apparent trajectory and location. Substantial small-scale variability in oceanographic and biological distributions suggests that such variability may play an important role in biogeochemical cycles. Data from the three projects provide a view of hydrographic variability in the Ross Sea that is impossible to obtain using traditional sampling. Multiplatform investigations are promising approaches to future polar experiments where logistical considerations are of paramount importance.